The Analysis of Imagery Aspects and Translation Strategies of Joko Pinurbo’s Poetry Anthology - Erwan, Erwan; Nur Ali, Achmad Juma Chatib (International Journal of Linguistics, Literature and Translation, 2022)
This study aims at describing imagery aspects and their English translation strategy in the poetry anthology “Celana” by Joko Pinurbo. The method of research is descriptive and qualitative. This study describes and analyses the imagery aspects of the poetry anthology “Celana” by Joko Pinurbo; Night Raid, Patrol, and Calvary. The subject of the research is the text which contains imagery aspects. In gathering the data, the researcher collected the data by using library research as well as documentation analysis focusing on the imagery aspects from the poetries. The analysis of the translation strategy used Chesterman’s translation strategy. The results of the study based on data analysis showed 1) the imageries found in the three poetries by Joko Pinurbo are visual imagery, auditory imagery, and kinesthetic imagery. The dominant one is visual imagery, 2) The translation strategies found in the English translation by Harry Aveling are explicitness change, literal translation, compression, expansion strategy, cultural filtering (adaptation), level shift, paraphrase, transposition, and information change (addition). The most dominant imagery is visual imagery, and the most dominant strategy is the literal translation strategy.